Evolution and Viability of Asian Horseshoe Crabs Appear Tightly Linked to Geo‐Climatic Dynamics in the Sunda Shelf - Qian Tang; Akbar John; Yusli Wardiatno; Shin Nishida; Van Tu Do; Xiaoyong Xie; Siddhartha Pati; Handoko Adi Susanto; Sukree Hajisamae; Bryan Raveen Nelson; Wah Wah Min; Mohammad Eusuf Hasan; et al. (Conservation Letters, 2025)
ABSTRACT Horseshoe crabs are unique living fossils that have remained almost unaltered through 400 million years of global change. They face rapid worldwide declines under increasing anthropogenic pressure. Using comprehensive geographic and genomic sampling combined with approaches that integrate DNA with environmental and climatic datasets, we assessed the population genetic structure, demographic histories, and vulnerability to future climate change in three out of four extant horseshoe crab species, all centered in Asia. Our study highlights that the Sunda Shelf, a complex and dynamic shallow‐marine landscape, has been the sole repository of most genetic diversity among all three Asian species, and therefore crucial to the long‐term survival of horseshoe crabs. Our study not only provides the first genomic baseline data for the evaluation of Asian horseshoe crabs’ conservation status but also identifies core habitats that potentially act as refugia and corridors for Asian horseshoe crab populations with impending anthropogenic global warming.